2018
DOI: 10.1257/pol.20160384
|View full text |Cite
|
Sign up to set email alerts
|

Trickle-Down Ethnic Politics: Drunk and Absent in the Kenya Police Force (1957–1970)

Abstract: How does ethnic politics affect the state’s ability to provide policing services? Using a panel of administrative personnel data on the full careers of 6,784 police officers, we show how the rise of ethnic politics around Kenya’s independence influenced policemen’s behavior. We  find a significant deterioration in discipline after Kenya’s first multiparty election for those police officers of ethnic groups associated with the ruling party. These effects are driven by a behavioral change among these policemen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It should be noted that while staffing changes would have taken time to take place, related staff behaviour may have changed rapidly. Vanden Eynde et al (2018) show, for instance, that the behaviour of public servants in Kenya changed in response to coethnic leadership in the post-independence period. It may also be the case that the health services simply being administered by co-ethnics was sufficient to change demand from users, particularly if they expected more favourable treatment as a result.…”
Section: Discussion Of Possible Mechanismsmentioning
confidence: 99%
“…It should be noted that while staffing changes would have taken time to take place, related staff behaviour may have changed rapidly. Vanden Eynde et al (2018) show, for instance, that the behaviour of public servants in Kenya changed in response to coethnic leadership in the post-independence period. It may also be the case that the health services simply being administered by co-ethnics was sufficient to change demand from users, particularly if they expected more favourable treatment as a result.…”
Section: Discussion Of Possible Mechanismsmentioning
confidence: 99%
“…This is widely the case whether it involves representative democracy or outright autocracy (Cheeseman, 2018a, 2018b; McCauley, 2017). Examples include Nigeria’s federalism that has had several setbacks instigated by ethnicity, religion and natural resource governance (Adamolekun and Kincaid, 1991; Bah, 2005; Diamond, 1988; LeVan, 2015; Obi and Oriola, 2018; Suberu, 1993), the unitary system of Kenya that was marred by ethno-clientelist grievances and political violence prior to the 2010 devolution (Fjelde and Höglund, 2018; Gutiérrez-Romero, 2010; Orr, 2019; Vanden Eynde et al, 2018) and the suppressive regime of Sudan’s Al Bashir that undermined non-Arab participation in public life until its downfall in 2019 (Arman, 2019; Elnaiem, 2019; Sefa-Nyarko, 2016a).…”
Section: Institutional Design Complexities In Multi-ethnic Statesmentioning
confidence: 99%
“…We focus our attention on Kenya as a type of most-likely crucial case study (Gerring 2007), such that Kenya is the place where we would most likely expect to find evidence of ethnic favouritism in education, given the extant literature on this topic (Kramon & Posner 2016; Li 2018). Indeed, there is currently more scholarship on ethnic and regional favouritism in Kenya than in any other individual sub-Saharan African country (Burgess et al 2015; Kramon & Posner 2016; Li 2018; Vanden Eynde et al 2018; Simson 2019), which is arguably due to the highly ethnicised nature of Kenyan politics as well as to its high-quality data, and the fact that it has experienced two ethnic presidential transitions which allow for a way to test these hypotheses. Thus the fact that we do not find evidence of ethnic favouritism in educational outcomes in Kenya suggests that the much broader literature on ethnic and regional favouritism deserves closer scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) have shown that African leaders seek to balance cabinet appointments amongst all larger ethnic groups, while Simson (2019) finds that public sector employees in Kenya and Uganda are more regionally representative than educational disparities alone would predict. Similarly, a historical study of the Kenyan police force in the early decades of independence found no evidence that ethnicity was linked to preferential treatment, although it did influence and embolden the behaviour of policemen (Vanden Eynde et al 2018). Finally, Kasara (2007) finds evidence that African presidents tend to tax the main cash crop products of their co-ethnics at a higher rate than other crops, suggesting a negative rather than a positive effect of being a co-ethnic of the president.…”
Section: Introductionmentioning
confidence: 99%